2010
DOI: 10.1038/hr.2010.221
|View full text |Cite
|
Sign up to set email alerts
|

Benidipine reduces albuminuria and plasma aldosterone in mild-to-moderate stage chronic kidney disease with albuminuria

Abstract: Benidipine inhibits both L-and T-type Ca channels, and has been shown to dilate the efferent arterioles as effectively as the afferent arterioles. In this study, we conducted an open-label and randomized trial to compare the effects of benidipine with those of amlodipine on blood pressure (BP), albuminuria and aldosterone concentration in hypertensive patients with mild-tomoderate stage chronic kidney disease (CKD). Patients with BPX130/80 mm Hg, with estimated glomerular filtration rate (eGFR) of 30-90 ml min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Our data with lower doses of spironolactone or eplerenone might be more practical. Calcium channel blockers decrease aldosterone synthesis in human adrenocortical cells [24] and in hypertensive patients [25]. Nakamura et al reported that eplerenone potentiates the protective effects of amlodipine against cardiovascular injury in salt-sensitive hypertensive rats independently of blood pressure [26].…”
Section: Discussionmentioning
confidence: 99%
“…Our data with lower doses of spironolactone or eplerenone might be more practical. Calcium channel blockers decrease aldosterone synthesis in human adrenocortical cells [24] and in hypertensive patients [25]. Nakamura et al reported that eplerenone potentiates the protective effects of amlodipine against cardiovascular injury in salt-sensitive hypertensive rats independently of blood pressure [26].…”
Section: Discussionmentioning
confidence: 99%
“…In hypertensive patients with mild to moderate chronic kidney disease. 13 After 48 weeks of treatment a significant and comparable reduction in systolic and diastolic BP in both the groups (p=<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that certain types of calcium channel blockers, including efonidipine [70], benidipine [71], azelnidipine [72], and cilnidipine [73], inhibit aldosterone synthesis in adrenocortical cells. Furthermore, clinical studies show that these agents decrease serum aldosterone levels in hypertensive patients [74][75][76][77][78][79]. Of interest, these calcium channel blockers are endowed with the ability to inhibit not only L-type but also T-type (efonidipine, benidipine, azelnidipine) or N-type calcium channels (benidipine, cilnidipine), whereas conventional calcium channel blockers such as nifedipine and amlodipine exert inhibitory action solely on L-type calcium channels [80][81][82].…”
Section: Aldosterone Blockade In Ckdmentioning
confidence: 99%